1981
DOI: 10.1071/ar9810497
|View full text |Cite
|
Sign up to set email alerts
|

The use of urea to improve milk yields and lamb survival of Merinos in a dry tropical environment

Abstract: Urea supplementation of lambing Merino ewes increased milk yield and lamb growth and survival rates in both pen and paddock studies. These productivity gains occurred in a semi-arid environment characterized by poor reproductive efficiency in Merinos. In pens, urea supplenlents fed to lactating ewes at the rate of c. 12 g/day stimulated intake of poor quality pasture hay (0.9 %nitrogen) by c. 30% and increased total nitrogen intake by c. 100%. Milk yield was improved by c. 50% and lamb growth rate by c. 140%. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Lamb weight is a function of birthweight (which in turn is a function of prenatal nutrition), sex, litter size, parental genetics, parity, stress during pregnancy 31 and lamb growth rate. For the first 8 weeks, lamb growth rate is largely dependent on ewe nutrition, weight, condition score and parity and thus milk yield, and on lamb appetite and sex, while after 8 weeks, pasture quality and availability to the lamb become increasingly important 32–35 . Under extensive grazing conditions, lambs frequently fail to reach the desirable target weaning weight even in good seasons, and if feed quantity and quality are not maintained after weaning, lambs can quickly drop below this weight.…”
Section: Discussionmentioning
confidence: 99%
“…Lamb weight is a function of birthweight (which in turn is a function of prenatal nutrition), sex, litter size, parental genetics, parity, stress during pregnancy 31 and lamb growth rate. For the first 8 weeks, lamb growth rate is largely dependent on ewe nutrition, weight, condition score and parity and thus milk yield, and on lamb appetite and sex, while after 8 weeks, pasture quality and availability to the lamb become increasingly important 32–35 . Under extensive grazing conditions, lambs frequently fail to reach the desirable target weaning weight even in good seasons, and if feed quantity and quality are not maintained after weaning, lambs can quickly drop below this weight.…”
Section: Discussionmentioning
confidence: 99%
“…However, the average forb content of the pasture in this paddock was low (5 kg/ha) so probably the majority of C 4 plants consumed were grasses. The nutritive value of grass in this environment {Astrebla spp., 4-9% CP, IVDMD 40-55%) declines quickly with senescence and dry pastures are nutritionally inadequate for maintaining lactating ewes (Stephenson et al 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Forbs (herbaceous plants other than grasses) generally constitute a minor proportion of total The high mortality of lambs between birth and lamb pasture biomass; however, the presence of lesser marking (36%) (Moule 1954) in north-west Queens-pasture constituents in the diet of sheep in the subland has been attributed to heat stress (Hopkins et al tropics (Weston & Moir 1969;Lorimer 1978;1980;Stephenson et al 1980) and poor nutrition McMeniman et al 1986), semi-arid environments (Stephenson et al 1981). The average ovulation rate (Leigh & Mulham 1964;Graetz & Wilson 1980; of ewes is 110% (Entwistle 1972), the pregnancy rate Squires 1980) and higher rainfall rangelands (Leigh & of ewes teased using testosterone-treated wethers is Holgate 1978) is significant in terms of productivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considerable research has confirmed the relationship between protein nutrition on one hand and the reproduction, pregnancy and lactation of livestock on the other, particularly consuming high protein legumes like alfalfa. High protein diets stimulate live weight gain or reduce live weight loss [9], while increasing ovulation rates [10], placental size [11], birth weight [12] and survival [13]. The increased birth weight possibly lowers the incidence of retained placenta, while milk yield and milk production efficiency are increased [14].…”
Section: Reproduction and Calf Performancementioning
confidence: 99%